Financial Performance, Exchange Rate, and Firm Value: The Indonesian Public Companies Case - Setiawanta, Yulita; Utomo, Dwiarso; Ghozali, Imam (Organizations and Markets in Emerging Economies, 2020)
Transactions between countries require a stable exchange rate. When the exchange rate of the country experiences uncertainty, then this will influence the company’s financial performance and even affect the company’s market value. This study aims to look for the direct influence of the company’s financial performance as an independent variable and the firm value as a dependent variable within the investor perspective, also including the exchange rate factor as a moderating variable. Investors could probably learn about information on the ups-and-downs of the Indonesian rupiah against foreign currencies before their investment decisions, even though financial performance substantially influences the company’s market value. The sample in this study was 50 companies within four years of observation. Data processing was carried out by the Eviews statistical application. The results showed that the financial performance, which is proxied by the capital structure, affects firm value, but not profitability. The impact of exchange rate moderation also occurs in the relationship of capital structure and firm value, while the moderation effect on profitability and firm value is not proven. This study provides information that exchange rates influence investment interests upon investors’ analysis of the financial performance of the capital structure, but not profitability.